The Adipokine Metrnl Ameliorates Chronic Colitis in Il-10–/– Mice by Attenuating Mesenteric Adipose Tissue Lesions During Spontaneous Colitis. (7th January 2019) - Zuo, Lugen; Ge, Sitang; Ge, Yuanyuan; Li, Jingjing; Zhu, Bing; Zhang, Zongbing; Jiang, Congqiao; Li, Jing; Wang, Suanhu; Liu, Mulin; Li, Shiqing; Wu, Rong; et al.
Abstract: Background: Crosstalk between mesenteric adipose tissue [MAT] and the intestines affects the progression of Crohn's disease [CD]. The adipokine metrnl regulates adipocyte function and has anti-inflammatory activity. We aimed to explore metrnl expression in CD MAT, investigate the influence of metrnl on the experimental colitis disease course and determine the mechanism underlying this effect. Methods: Metrnl expression in MAT specimens obtained from patients with and without CD was tested by immunohistochemistry. Male Il-10 –/– mice with spontaneous enteritis were divided into positive control and metrnl-treated [Metrnl-Fc, 10 mg/kg/d, intraperitoneally, 8 weeks] groups. Age-matched male wild-type [WT] mice were used as negative controls. The effects of metrnl on enteritis and mesenteric lesions and the potential controlling mechanisms were evaluated. Results: Metrnl expression was higher in human CD MAT than in control MAT. Systemic delivery of metrnl significantly ameliorated chronic colitis in Il-10 –/– mice, as demonstrated by decreases in the disease activity index, inflammatory score and proinflammatory mediators. The protective effects of metrnl on MAT included reduced mesenteric hypertrophy, increased adipocyte size, improved adipocyte intrinsic function and ameliorated inflammation. Metrnl treatment activated STAT5/PPAR-γ signaling and promoted adipocyte differentiation in the MAT. Conclusions: Metrnl expression was increased in the MAT of CD patients. Metrnl administration attenuated mesenteric lesions by promoting adipocyte function and differentiation partly through STAT5/PPAR-γ signaling pathway activation, thereby ameliorating CD-like colitis in mice.